RECENT DEVELOPMENTS IN DATA RECORDING SYSTEMS FOR PHYSIOLOGY - Simonetta, Giuseppe; Aziz, Nauman; Simonetta, Giuseppe; Forrester, Kellie (Pakistan Journal of Physiology, 2006)
Data recording devices play a major role in Physiology research and teaching. These devices are used to record and analyze various human and animal physiological parameters such as temperature, blood pressure, electrocardiograms , respiration, blood flow, muscle activity and brain activity. In teaching, recording and analyzing these parameters help students learn about normal physiological functions of the body as well as being useful in understanding the changes that occur during disease data recording devices have improved rapidly as the technology has become more advanced. These have been evolved from kymographs, to chart recorders and polygraphs to more advanced computer based systems. The computer based data recording devices have not only reduced in size but have also improved in recording and analyses, applications and efficiency. A growing body of evidence from classroom assessment supports the effectiveness of computerized data recording system in self-learning, motivation and improved performance and skills development in undergraduate courses of various disciplines. There has been a lot of debate going on whether to use computer simulation or real experiments to be performed on computer-based systems in a teaching setup to provide hands-on experience. Both approaches have merits and demerits. However, it is essential to provide hands-on experience to students as much as possible. Most of the institutions in developed countries offering human and animal physiology courses have adapted to new computer based tools for teaching and research but in developing countries such as Pakistan, this trend is growing at slow pace because of several reasons.